Pharmacologically induced absence seizures versus kindling in Wistar rats - ONAT, FİLİZ (KARE PUBL, 2019)
OBJECTIVE: This study aimed to investigate the effects of gamma-butyrolactone (GBL), a prodrug of gamma-Hydroxybutyric acid-induced absence seizures on the development of kindling in Wistar rats. METHODS: Three groups of adult male Wistar rats under anesthesia were implanted with bilateral cortical recording elec- trodes for the GBL group (GBL) and/or bipolar stimulation electrodes into the right basolateral amygdala for the Kindling group (KI) alone and Kindling plus GBL group (GBL+KI). Rats in the KI and GBL+KI groups were stimulated twice daily at the afterdischarge threshold until they reached Racine's stage 5 seizure state. The animals in the GBL + group had an i.p injection of GBL 20 minutes before each electrical stimulation, and the effects of GBL-induced seizures on the development of kindling were investigated. The animals in the GBL group were injected GBL twice daily i.p. for 15 days without receiving any electrical stimulation. RESULTS: The KI animals reached stage 5 seizure stage at 12th stimulations, whereas the GBL+KI rats reached at 27th stimulations. The mean numbers of stimulations needed for the development of the first stage 3, 4, or 5 generalized seizures were significantly higher in the GBL+KI group than the KI group. CONCLUSION: The resistance to amygdala kindling in the GBL model can be modulated by the absence seizure mechanism alone, without the intervention of an abnormal genetic background.
Keywords: Amygdala; gamma-butyrolactone; experimental limbic epilepsy; genetic absence epilepsy; kindling; GAMMA-HYDROXYBUTYRATE MODEL; ELECTRICAL-STIMULATION; ANIMAL-MODELS; EPILEPSY; BRAIN; BUTYROLACTONE; ACID; MECHANISMS; RESISTANCE; INJECTION